The learning styles amongst lifelong learners in Sekolah Pondok according to KOLB learning style inventory (KLSI) in Penang, Malaysia - Zahari Hamidon,; Hamidah Mat,; Khairul Hamimah Mohammad Jodi,; Zulaika Zakariah, (2019)
Lifelong learning and experiential learning, two separate terms but relatively having the same meaning. The nature of the learners in lifelong learning is well received as enjoying the journey towards the pursuit of knowledge for both personal and professional purposes. Experiential learning involves experiences in the learning process supported by reflection. At OUM, most of the learners are working adults. Lifelong learning is well connected with experiential learning regarding the learning process. This study intends to observe the views of lifelong learners from the perspective of experiential learning by Kolb (2017). The study aims to determine the types of learning styles practiced by lifelong learners in Sekolah Pondok Sg. Bakap, Seberang Prai. The views from the lifelong learners in Sekolah Pondok Pondok Tuan Guru Haji Yusoff, Sg. Bakap, Seberang Prai are gathered and fit in the Nine Learning Styles of the Kolb Learning Style Inventory Version 4.0 (KLSI 4.0). Qualitative approaches are used by triangulation techniques to ensure that the information obtained is more accurate, valid and reliable, then measured through the determiners adapted from Kolb & Kolb (2017). The findings based on the qualitative data shows that the learning styles have fulfilled most of the KLSI, some of the evidence seems to be unique due to the nature of the programme. It enables us to understand the process of learning and their unique method of learning. By strengthening the realisation of how they learn will create insights on the level of metacognitive control of their learning process, hence will enable us to create the rubric as a guide in designing the lesson on online learning at OUM. (Abstract by authors)